K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

7 tháng 11 2021

\(\text{ 32-2.(5+x)=6}\)

\(2.\left(5+x\right)=32-6\)

\(2.\left(5+x\right)=26\)

\(\left(5+x\right)=26:2\)

\(5+x=13\)

\(x=13-5\)

\(\Rightarrow x=5\)

7 tháng 11 2021

  2. (5 + x) = 32 - 6 = 26 

       5 + x = 26 : 2 = 13

              x = 13 - 5 = 8

                - ht -

6 tháng 8 2016

3/2+5/4+9/8/+17/16+33/32-6+x-1/x+1=31/32-2/2015

=(1+1/2)+(1+1/4)+(1+1/8)+(1+1/16)+(1+1/32-6+x-1/x+1=31/32-2/2015

=(1/2+1/4+1/8+1/16+1/32)+(1+1+1+1+1)-6+x-1/x+1=31/32-2/2015

=31/32+5-6+x-1/x+1=31/32-2/2015

=5-6+x-1/x+1=31/32-2/2015-31/32

=-1+x-1/x+1=-2/2015

=x-1/x+1=-2/2015- -1

=x-1/x+1=2013/2015

=>x=2014

14 tháng 1 2021

x + 5 x 2 - ( 32 + 16 x 3 : 6 - 15 ) = 0

x + 5 x 2 - 25 = 0

x + 5 x 2 = 0 + 25

x + 5 x 2 = 25

x + 10 = 25

x = 25 - 10 

x = 15

1 tháng 2 2019

a , 32 - 2 ( x + 1 ) = 42

2 ( x + 1 ) = 32 - 42

2 ( x + 1 ) = -10

x + 1 = -10 : 2 = -5

x = -5 - 1 = -6

b, 12 - 5 (x + 2 ) = 32

5 ( x + 2 ) = 12 - 32 = -20

x + 2 = -20 : 5 = -4

x = -4 - 2 = -6

1 tháng 2 2019

c , 14 - 5 ( x + 4 ) = 9

5 ( x + 4 ) = 14 - 9

5 ( x + 4 ) = 5

x + 4 = 5 : 5 = 1

x = 1 - 4 = -3

d , 24 - 6 ( 2x + 1 ) = 6

6 ( 2x + 1 ) = 24 - 6

6 ( 2x + 1 ) = 18

2x + 1 = 18 : 6

2x + 1 = 3

2x = 3 - 1 = 2

x = 2 : 2 = 1

3 tháng 7 2017

a, 10 + 2x = 45 ÷ 43

10 + 2x = 45/43

2x = 45/43 - 10

2x = -385/43

x = -385/43 ÷ 2

x = -385/86

b, 2x - 138 = 23.32

2x - 138 = 736

2x = 736 + 138

2x = 874

x = 874 ÷ 2

x = 437

c, 231 - ( x - 6 ) = 1339 ÷ 13

231 - ( x - 6 ) = 103

x - 6 = 231 - 103

x - 6 = 128

x = 128 + 6

x = 134

d, x + 5.2 - ( 32 + 16.3 ÷ 6 - 15 ) = 0

x + 10 - 25 = 0

x + 10 = 0 + 25

x + 10 = 25

x = 25 - 10

x = 15

3 tháng 7 2017

a) 10 + 2 . x = 45 : 43

            2 . x = 45/43 -10

            2 . x = -385/43

                 x = -385/43 : 2

                 x = -385/86

b) 2 . x - 138 = 23 . 32

    2 . x - 138 = 736

             2 . x = 736+138

             2 . x = 874

                  x = 874 : 2

                  x = 437

c) 231 - (x -6) = 1339 : 13

    231 - (x -6) = 103

               x - 6 = 231 -103

               x - 6 = 98

                    x = 98 +6

                    x = 104

d) x + 5 . 2 - (32 +16 . 3 : 6 - 15) = 0

        x + 5 . 2 - (32 + 48 : 6 - 15) = 0

               x + 5 . 2 - (32 + 8 - 15) = 0

                               x + 5 . 2 - 25 = 0

                               x + 10 - 25 = 0

                                      x + 10 = 0 + 25

                                      x + 10 = 25

                                              x = 25 - 10

                                              x = 15